The Heritage Arabic Text For Learning And Knowledge Acquisition/ النص العربي التراثي للتعلم واكتساب المعرفة - Alae Echatar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Heritage is a significant tributary of learning and knowledge acquisition in modern communities. Heritage research is of many advantages. It could pave the way to evaluate the past, learn from its mistakes, and benefit from its positive aspects to build the future successfully. This research aims to examine the most important theoretical frameworks that deal with the subject, derive a correct intellectual model in dealing with the heritage text, and highlight the most prominent academic problems and obstacles that prevent the proper dealing with the heritage text in understanding and acquisition. This research uses a comparative approach to assess three intellectual models, extract their key characteristics, and analyze each model, enabling a comprehensive comparison highlighting their most significant features. The results of this study: 1. The most important theoretical frameworks that deal with the heritage of Arabic text are the models of Abed Aljabri, Fahmī Jadʻān, and Ṭāhā ʻAbd al-Raḥmān. 2 The model of Ṭāhā ʻAbd al-Raḥmān is the accurate and comprehensive intellectual framework for dealing with the heritage text. 3. The most prominent academic problems and obstacles that hinder a proper understanding and acquisition of the heritage text are the issue of methodology and objectivity, the challenge of avoiding preconceived notions, and the utilization of pre-existing theoretical and methodological frameworks without considering the unique nature of the text.